EVALUASI PENERIMAAN PENGGUNA COMPUTER BASED TEST DENGAN PENDEKATAN TAM DI KULON PROGO - Sukasna .; Kusrini .; Sudarmawan . (Universitas Muhammadiyah Ponorogo, 2017)
Implementation of national examinations in junior high, high school / vocational equivalent is implemented by the Ministry of Education and Culture of the Republic of Indonesia is always changing, both in terms of benefits, technical implementation, the number of package models matter up with ways of correcting the results of the exam. Along with the technological development of national examinations now begin to be implemented by means of a computer on-line or better known as Computer Based Test (CBT). The purpose of this study was to examine the effect: the experience of the perception of usefulness and ease; complexity to the perception of usefulness and ease; the suitability of tasks to perception of usefulness and ease; perceived ease the perception of usefulness; perceptions of the usefulness of the attitude of users; perceived ease of the attitude of users; perceptions of the usefulness of the behavior of interest; user attitude towards the behavior of interest; behavior towards the use of real interest in the use of CBT. The approach used in this study is the Technology Acceptance Model (TAM) I think Davis (1989) with SEM method PLS program to test the hypothesis in this study using SEM Based Component Analysis or Partial Least Square (PLS). The results obtained from this study finding significant influence and no significant external variables as well as some of the perceptions that influence the implementation of CBT in Kulon Progo.Implementation of national examinations in junior high, high school / vocational equivalent is implemented by the Ministry ofEducation and Culture of the Republic of Indonesia is always changing, both in terms of benefits, technical implementation, thenumber of package models matter up with ways of correcting the results of the exam. Along with the technological development ofnational examinations now begin to be implemented by means of a computer on-line or better known as Computer Based Test (CBT).The purpose of this study was to examine the effect: the experience of the perception of usefulness and ease; complexity to theperception of usefulness and ease; the suitability of tasks to perception of usefulness and ease; perceived ease the perception ofusefulness; perceptions of the usefulness of the attitude of users; perceived ease of the attitude of users; perceptions of the usefulnessof the behavior of interest; user attitude towards the behavior of interest; behavior towards the use of real interest in the use of CBT.The approach used in this study is the Technology Acceptance Model (TAM) I think Davis (1989) with SEM method PLS program totest the hypothesis in this study using SEM Based Component Analysis or Partial Least Square (PLS). The results obtained from thisstudy finding significant influence and no significant external variables as well as some of the perceptions that influence theimplementation of CBT in Kulon Progo.